MINIMUM WAGE POLICY IN MALAYSIA AND LEGAL CHALLENGES IN THE HOTEL INDUSTRY (UUM Journal of Legal Studies, 2026)
The Minimum Wage Order, introduced by the Malaysian government, aims to protect employees’ welfare and well-being by ensuring that wages are sufficient to meet the cost of living. This article evaluates the purpose of the latest minimum wage in Malaysia, particularly its role in helping employees cope with current living costs, while also examining the impacts of its implementation on both employers and employees in the hotel industry. Legal challenges surrounding the determination of basic wages in this sector are analysed through court rulings and legal precedents, with a critical analysis drawing on relevant literature, legislation, and case law. Our findings reveal that disputes in the hotel industry often arise over whether service charges should be treated as part of the basic wage, an issue that has repeatedly led to legal challenges and court interventions. In the Crystal Crown Hotel case, the Federal Court affirmed that service charges should not be counted as part of the basic wage, with the practical implication that hotel employees are entitled to a basic salary—protected under the minimum wage framework—in addition to service charges. By situating the minimum wage debate within case law and legal precedents, this article provides practical insights for policymakers, industry stakeholders, and legal practitioners, while offering original perspectives on strengthening wage protection and reducing conflicts in Malaysia’s labour market.
Keywords: Minimum wage order; wage protection; hotel industry; service charges; Malaysia labour law